Dedicated mass-casualty incident hospitals: An overview. Issue 2 (February 2017) - Haverkort, J.J. Mark; de Jong, Mirjam B.; Foco, Maurizio; Gui, Daniele; Barhoum, Masad; Hyams, Gila; Bahouth, Hany; Halberthal, Michael; Leenen, Luke P.H.
Abstract: Introduction: Hospitals worldwide are preparing for mass casualty incidents (MCIs). The Major Incident Hospital in the Netherlands was constructed 25 years ago as a dedicated hospital for situations wherein a sudden increase in medical surge capacity is mandated to handle an MCI. Over the years, more initiatives of dedicated MCIs have arisen. Herein, we compared the MCI facilities from three countries considering the reasons for construction and the functionality. Methods: Three dedicated mass casualty hospitals and one hospital with a largely fortified structure were compared. The centres were located in the Netherlands, Italy, and Israel. Between August 2015 and January 2016, structured interviews were conducted with representatives of the hospitals' medical operations. The interviews focussed on general information regarding the need for MCI preparedness and scenarios that require preparation, reasons for construction, hospital missions, and the experiences gained including training. Results: All dedicated MCI hospitals had a common policy wherein they sought to create normal work circumstances for the medical staff by using similar equipment and resources as in normal hospitals. The MCI hospitals' designs differed substantially, as determined by the threats faced by the country. In Europe, these hospitals are designed as a solution to surge capacity and function as buffer hospitals offering readily available, short term, additional medical capacity to the local health care system. Israel faces constant threat from long-term conflicts; during the 2006 war, several hospitals suffered direct missile impacts. Therefore, Israeli MCI hospitals are designed to be fortified structures offering shelter against both conventional and non-conventional warfare and intended as a long-term solution during siege situations. Conclusion: Several dedicated MCI hospitals are presently being constructed. During construction, the local circumstances should be taken into account to determine the functionality for both short-term solutions for surge capacity and as fortified structures to withstand under-siege situations.